Донбасс и Галичина в региональной системе Украины - Кононов, И.; Хобта, С.; Щудло, С. (Социология: теория, методы, маркетинг, 2008)
The article examines cognitive aspects of regional sociology when analyzing the regional system of Ukraine. It is shown that Ukraine is structured not only according to the relations between center and provinces, but also between two regional poles, namely Donbass and Galychyna that produce different perspectives on social development. Interaction between these regions gives a special dynamism to the regional system of Ukraine.